Unraveling the Limits of Mitochondrial Control Region to Estimate the Fine Scale Population Genetic Differentiation in Anadromous Fish Tenualosa ilisha. (25th May 2016) - Verma, Rashmi; Singh, Mahender; Kumar, Sudhir
Abstract : The mitochondrial control region has been the first choice for examining the population structure but hypervariability and homoplasy have reduced its suitability. We analysed eight populations using control region for examining the population structure of Hilsa . Although the control region analysis revealed broad structuring between the Arabian Sea and Bay of Bengal (F S T     0.0441, p < 0.001 ) it was unable to detect structure among riverine populations. These results suggest that the markers used must be able to distinguish populations and control region has led to an underestimation of genetic differentiation among populations of Hilsa .